2017
DOI: 10.1002/ar.23558
|View full text |Cite
|
Sign up to set email alerts
|

Hominin Hip Biomechanics: Changing Perspectives

Abstract: The shape of the human pelvis reflects the unique demands placed on the hip abductor muscles (gluteus medius and gluteus minimus), which stabilize the body in the frontal plane during bipedal locomotion. This morphological shift occurred early in hominin evolution, yet important shape differences between hominin species have led to significant disagreement about abductor function and locomotor capability in these extinct taxa. A static biomechanical model that relies on a close association between skeletal mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 104 publications
(234 reference statements)
0
18
0
Order By: Relevance
“…Washburn 29 proposed that further widening of the pelvis would impede bipedal gait, but recent biomechanical studies did not support this hypothesis ( Figure 5). Warrener and colleagues 33,34 showed that females and males do not differ in efficiency in either walking or running on a treadmill ( Figure 5). The kinematic study of Whitcome et al 35 showed that during walking at higher speed, females translate more of the pelvic rotation into strides than males, which leads to similar efficiency of locomotion despite wider hips.…”
Section: Expert Reviewsmentioning
confidence: 98%
“…Washburn 29 proposed that further widening of the pelvis would impede bipedal gait, but recent biomechanical studies did not support this hypothesis ( Figure 5). Warrener and colleagues 33,34 showed that females and males do not differ in efficiency in either walking or running on a treadmill ( Figure 5). The kinematic study of Whitcome et al 35 showed that during walking at higher speed, females translate more of the pelvic rotation into strides than males, which leads to similar efficiency of locomotion despite wider hips.…”
Section: Expert Reviewsmentioning
confidence: 98%
“…Washburn provided a classic conceptualization of this interaction in his phrase “the obstetric dilemma” (OD), by which women experience difficult childbirth today because postural and obstetrical considerations came into conflict in human evolutionary history (Washburn, 1960). Critics argue that the notion of a uniform human OD across populations fails to satisfactorily explain the relationship between difficult childbirth today and the way the human female pelvis evolved (Dunsworth, Warrener, Deacon, Ellison, & Pontzer, 2012; Gruss, Gruss, & Schmitt, 2017; Rosenberg & Trevathan, 1995; Wall‐Scheffler & Myers, 2017; Walrath, 2003; Warrener, 2017; Warrener, Lewton, Pontzer, & Lieberman, 2015; Wells, DeSilva, & Stock, 2012; Whitcome, Miller, & Burns, 2017). Further, wide variation in pelvic dimensions exists across populations (reviewed in Betti, 2017; Betti & Manica, 2018), and is influenced by many factors (Auerbach, King, Campbell, Campbell, & Sylvester, 2018; Betti, 2017; Betti, von Cramon‐Taubadel, Manica, & Lycett, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Quantifying human morphological (musculoskeletal) variation is at the heart of biological anthropology. For example, human (and hominin) pelvic morphology has a profound influence on bipedal capabilities [14,80], and has been the focus of intense scrutiny [41,81,82]. Humans are known to be sexually dimorphic in pelvic size and shape [83][84][85].…”
Section: Human Variabilitymentioning
confidence: 99%
“…muscle, joint contact) forces. Finite-element analysis of skeletal elements [38,39], estimating locomotor costs [40,41] and evaluating task performance [42,43] all require muscle forces to be known or estimated. Measuring muscle and joint contact forces in living animals is, however, exceptionally challenging because it requires surgical intervention to implant the relevant sensors into the body [44,45].…”
Section: Introductionmentioning
confidence: 99%